Epidemiology, clinical presentation, risk factors, intensive care admission and outcomes of invasive meningococcal disease in England, 2010–2015. Issue 26 (18th June 2018) - Parikh, Sydel R.; Campbell, Helen; Gray, Stephen J.; Beebeejaun, Kazim; Ribeiro, Sonia; Borrow, Ray; Ramsay, Mary E.; Ladhani, Shamez N.
Abstract: The epidemiology of invasive meningococcal disease (IMD) is constantly changing as new strains are introduced into a population and older strains are removed through vaccination, population immunity or natural trends. Consequently, the clinical disease associated with circulating strains may also change over time. In England, IMD incidence has declined from 1.8/100, 000 in 2010/2011 to 1.1/100, 000 in 2013/2014, with a small increase in 2014/2015 to 1.3/100, 000. Between 01 January 2011 and 30 June 2015, MenB was responsible for 73.0% (n = 2489) of 3411 laboratory-confirmed IMD cases, followed by MenW (n = 371, 10.9%), MenY (n = 373, 10.9%) and MenC (n = 129, 3.8%); other capsular groups were rare (n = 49, 1.4%). Detailed questionnaires were completed for all 3411 laboratory-confirmed cases. Clinical presentation varied by capsular group and age. Atypical presentations were uncommon (244/3411; 7.2%), increasing from 1.2% (41/3411) in children to 3.5% (120/3411) in older adults. Known IMD risk factors were rare (18/3411; 0.5%) and included complement deficiency (n = 11), asplenia (n = 6) or both (n = 1). Nearly a third of cases required intensive care (1069/3411; 31.3%), with rates highest in adults. The 28-day CFR was 6.9% (n = 237), with the lowest rates in 0–14 year-olds (85/1885, 4.5%) and highest among 85+ year-olds (30/94, 31.9%). These observations provide a useful baseline for the current burden of IMD in a European country with enhanced national surveillance.